Sin : selected poems of Forugh Farrokhzad - Farrukhzād, Furūgh (University of Arkansas Press, 2007)
Sholeh Wolp©♭ is the author of The Scar Saloon and Rooftops of Tehran . Her poems, translations, essays, and reviews have appeared in many publications.